Managing Digital Presence: A Comparative Cost-Benefit Analysis of Onsite and Remote Operational Models - Tamayo, Josan D.; Ayo, Eliza B.; Chua, Joey O.; Natino, Czarina Mitz (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Organizations face critical decisions regarding work models for digital presence management (DPM) teams, where onsite and remote operations present distinct trade-offs in cost, security, collaboration, and engagement. This study developed and compared scenario-based cost-benefit models for four staffing configurations (30, 60, 90, 150 workers) across onsite and remote DPM operations. We employed a scenario-based comparative analysis using projected operational data for hardware, software, licensing, staffing, and infrastructure costs (denominated in PHP). Social media engagement projections were based on a 3.5% organic reach rate, benchmarked to the dominant Philippine platform, Instagram. Sensitivity analysis was included. Remote operations demonstrated 21–28% monthly cost savings (PHP 669,850–1,337,250 vs. PHP 850,600–1,860,600 onsite). Cost per 1,000 projected reach was lower for remote models (PHP 2.66–3.18) compared to onsite (PHP 3.37–4.43). Onsite models incurred substantial upfront infrastructure costs (PHP 532,428–2,002,256). While remote DPM offers significant cost advantages, achieving equivalent security requires investment in advanced frameworks, which may offset a portion of the savings. The decision framework must therefore prioritize organizational security requirements, governance needs, and budget constraints alongside cost efficiency.